Multidimensionality of Land Ownership among Men and Women in Sub-Saharan Africa - Hasanbasri, Ardina; Kilic, Talip; Koolwal, Gayatri; Moylan, Heather (World Bank, Washington, DC, 2022)
Across Sub-Saharan African countries with customary tenure systems and low levels of documented land ownership, there are limited nationally representative insights on men and women landowners’ rights over land. Variations in institutions and norms governing land ownership further complicate cross-country comparisons. Using machine learning techniques and nationally representative, intrahousehold survey data elicited in private from men and women on their ownership of assets, this paper creates unique profiles of landowners in Ethiopia, Malawi, and Tanzania, anchored in a range of constructs related to self-reported rights and control over land parcels. The analysis reveals a high degree of cross-country consistency in the new insights. Landowners, particularly women, often do not have full rights and decision-making power over land. Multiple correspondence analysis demonstrates that transfer rights (rights to bequeath, sell, rent out, and use as collateral) contribute the most to the variation in the composition of the constructs related to rights and control over land. Hierarchical clustering shows that landowners can effectively be clustered into three categories: (1) owners with mostly exclusive transfer rights, (2) owners with mostly joint transfer rights, and (3) owners with no/limited transfer rights. Owners with transfer rights tend to have all other rights and measures of control. Women are overrepresented in the cluster of landowners with no/limited transfer rights, and in moving from the cluster with mostly joint transfer rights to the one with mostly exclusive transfer rights, the increase in the share of individuals not needing permission to exercise any right is considerably greater among women than men.